Endovascular Management of Brain Arteriovenous Malformation (AVM) Presenting with Contralateral Morbid Tinnitus: A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Brain arteriovenous malformations are type of intracranial high-flow vascular malformation that can present with incidental finding in asymptomatic patients, seizures, headache, ischemic events due to vascular steal from normal brain, hemorrhage. Pulsatile tinnitus is the result of blood flow related sounds transmitted to the inner ear and coincides with heartbeat. AVMs are a rare cause of pulsatile tinnitus which contributes to less than 1% of published cases in the literature. We report a case of morbid tinnitus due to brain AVM which was resolved completely by endovascular embolization of the lesion.J Bangladesh Coll Phys Surg 2022; 40: 128-131